The School for us and us for the School - Xisto, S.; Catarino, D. (Open Schools Journal for Open Science, 2020)
The main purpose of this project was to make the school more appealing, by working in the greenhouse, green spaces and leisure places. Transforming the school and making it a more active and welcoming place, was, from the beginning, the problem that was identified by the students. In their opinion, the school looked a little sad and they knew they would need help to transform it into a better place, where they could feel like home. With this purpose in mind, students attended a meeting with the local authorities and the Parents’ Association. To start the project, students made healthy gums to offer to other students, on Valentine’s Day, and they also made soaps to sell to the community. These activities allowed us to begin the greenhouse project. The occupation of these young people’s free time became different and it was a very enriching experience. The seed of the OSOS project is germinating, and we believe that, in the future, it will continue to give beautiful flowers. Together we were able to make the difference!